1996
DOI: 10.1016/s0896-6273(00)80177-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotypes of Different MPZ (P0) Mutations May Include Charcot–Marie–Tooth Type 1B, Dejerine–Sottas, and Congenital Hypomyelination

Abstract: Hereditary demyelinating peripheral neuropathies consist of a heterogeneous group of genetic disorders that includes hereditary neuropathy with liability to pressure palsies (HNPP), Charcot-Marie-Tooth disease (CMT), Dejerine-Sottas syndrome (DSS), and congenital hypomyelination (CH). The clinical classification of these neuropathies into discrete categories can sometimes be difficult because there can be both clinical and pathologic variation and overlap between these disorders. We have identified five novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
260
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 349 publications
(272 citation statements)
references
References 49 publications
10
260
1
1
Order By: Relevance
“…Moreover, it has been shown that Ser63del MPZ acts as a dominant negative that also results in wild‐type MPZ retention in the ER24; as such reducing S63del translation may permit more wild‐type MPZ to be released to reach the myelin membrane. Fifty percent of normal MPZ is known to be adequate for normal myelin formation as haploinsufficiency of MPZ does not cause a clinical neuropathy in patients 25, 26. Whether less than 50% of normal MPZ will also permit compact myelin formation is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that Ser63del MPZ acts as a dominant negative that also results in wild‐type MPZ retention in the ER24; as such reducing S63del translation may permit more wild‐type MPZ to be released to reach the myelin membrane. Fifty percent of normal MPZ is known to be adequate for normal myelin formation as haploinsufficiency of MPZ does not cause a clinical neuropathy in patients 25, 26. Whether less than 50% of normal MPZ will also permit compact myelin formation is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…CMT1B is associated with mutations in the myelin protein zero (MPZ) gene on chromosome 1q22 -q23 (Hayasaka et al, 1993;Latour et al, 1995). Three clinical and electrophysiological phenotypes have been associated with MPZ gene mutations: CMT1B, which is characterized by slow MNCV (, 25 m/s) and onset in the first two decades of life, Dejerine -Sottas syndrome with onset in infancy and extremely reduced MNCV (, 10 m/s), and congenital hypomyelination (Warner et al, 1996). However, several axonopathies in CMT disease have been associated with a mutation in the MPZ gene (Marrosu et al, 1998;Chapon et al, 1999;Mastaglia et al, 1999;Misu et al, 2000;Senderek et al, 2000;Young et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This adhesion molecule belongs to the immunoglobulin superfamily and fulfills multiple functions during myelin development and maintenance. Studies have revealed a number of mutations in the P0 gene that appear to be causal of human genetic neuropathies, such as Charcot-Marie-Tooth disease type 1B or Dejerine-Sottas disease [1,2,15]. Mice with a homozygous null mutation in the gene for P0 (P0 -/-) typically develop overt signs of peripheral neuropathy within one month after birth [11,12].…”
Section: Introductionmentioning
confidence: 99%